Makna Persembahan Korban Sebagai Penghapus Dosa Berdasarkan Efesus 2:5-9 Dan Implikasinya Bagi Orang Percaya Masa Kini - Beriaman Ndruru; Geri Nubatonis; A. Martha Anjeli (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
Sacrificial offerings are something that cannot be separated from the beliefs of every believer. Christ willingly died on the cross to redeem His people. Therefore, how important the sacrifice of Jesus Christ is for humanity. For that, it is very important to understand the meaning of the sacrifice of penance. The meaning of the sin offering is an admission of guilt before God. the meaning of the sin offering must be known from the old and new testaments, namely the sin offering. The sin offering in the Old Testament was the sacrifice of a lamb to take away the sins of God's people. In the new covenant, the sin offering is Jesus Christ, who died on the cross as a sin offering in Ephesians 2:5-9. Therefore, it is very important for believers today to know and understand the true sacrifice and sin offering.